Speaking and Singing: Or how Ultra-Orthodox Calvinists Tune their Bodies - Verrips, Jojada (Jaarboek voor liturgieonderzoek, 2013)
This article brings up the extraordinary paradox of pietistic language use, especially in its (half) chanted form: its power to both express religious knowledge and - more importantly - to evoke mystical, ecstatic or even trance-like experiences at the same time.